Hypolipidemic and antioxidant activities of Trichosanthes kirilowii maxim seed oil and flavonoids in mice fed with a high‐fat diet. Issue 8 (1st June 2020) - Hou, Zongkun; Zhu, Liancai; Meng, Run; Wang, Bochu
Abstract: Trichosanlhes kirilowii Maxim seed oil (TSO) is rich in conjugated linolenic acids, and the flavonoids (FLA) combined with n‐3 fatty acids can effectively change the plasma antioxidant capacity. Hyperlipidemia and oxidative stress are one of the most important risk factors for cardiovascular disease. This study aims to evaluate the effect of the TSO, FLA, and TSO combined with FLA (TSOFLA) intake on hyperlipemia mice. TSO and TSOFLA administration resulted in a significant decline in serum levels of total cholesterol, triglycerides, and low density lipoprotein‐cholesterol. TSOFLA improved the hepatic and serum antioxidant status as assessed by superoxide dismutase, glutathione peroxidase activities, and reduced the levels of lipid peroxidation. Hematoxylin‐eosin staining of liver and aorta tissue has shown a marked reduction of the hyperlipidemia‐induced lesions by gavage TSOFLA. Compared with TSO and FLA, TSOFLA has more significant hypolipidemic and antioxidant activities, which effects may be correlated to the synergy between TSO and FLA. Practical applications: Dyslipidemia is a common metabolic disorder, which is characterized by triglyceride levels increased, total cholesterol, and low‐density lipoprotein cholesterol. Lipid‐lowering treatment can reduce the expansion of coronary atherosclerosis, and particular the dietary lipids have important roles in controlling the concentrations of these risk factors. This is the first study evaluating the hypolipidemic and antioxidant activities effects of Trichosanlhes kirilowii Maxim seed oil (TSO), flavonoids (FLA), and TSO combined with FLA (TSOFLA) intake on hyperlipemia mice caused by a high‐fat diet. The pharmacological effects of dietary TSOFLA are correlated to its high content of unsaturated fatty acids and flavonoids. This information can be of interest to the development of food supplements in the field of diseases associated with high‐fat intakes such as cardiovascular diseases and adiposis. Abstract : Trichosanlhes kirilowii Maxim seed oil (TSO) combined with flavonoids (FLA) (TSOFLA) administration resulted in a significant decline in serum levels of total cholesterol, triglycerides, and low density lipoprotein‐cholesterol. TSOFLA improved hepatic and serum antioxidant status as assessed by superoxide dismutase, glutathione peroxidase activities and reduced levels of lipid peroxidation. Compared with TSO and FLA, TSOFLA has more significant hypolipidemic and antioxidant activities, which effects may be correlated to the synergy between TSO and FLA.